Immunomodulatory Effect of G2013 (α-L-Guluronic Acid) on the TLR2 and TLR4 in Human Mononuclear Cells - Sharifi, Laleh; Mohsenzadegan, Monireh; Aghamohammadi, Asghar; Rezaei, Nima; Zavareh, Farzaneh T.; Bokaie, Saied; Moshiri, Mona; Aghazadeh, Zahra; Norouzbabaie, Zahra; Azizi, Gholamreza; Mirshafiey, Abbas (Current Drug Discovery Technologies, 2018)
Background: Inhibition of Toll-like receptors (TLRs) signaling has been established as a new method for the development of anti-inflammatory drugs instead of NSAIDs (non-steroid anti-inflammatory drugs). Since the immunomodulatory role of G2013 (α-L-Guluronic acid) was reported in some recent experiments, we decided to assess the effects of G2013 on the protein expression of TLR2 and TLR4, their downstream signaling cascade, and the secretion of pro-inflammatory cytokines in human peripheral blood mononuclear cells (PBMCs). Methods: After blood sampling from 16 healthy donors, PBMCs were isolated and treated with/without lipopolysaccharide (LPS), lipopolyteichoic acid (LTA), and G2013. Flow cytometry was done for detecting the protein expression of TLR2 and TLR4. MyD88, IΚB, Tollip, and NF-ΚB mRNA expression were assessed by realtime PCR. ELISA was performed for assessing the concentration of IL-1β and IL-6. Results: G2013 at a concentration of 25 μg/mL (high dose) significantly downregulated NF-ΚB, IΚB and MyD88 mRNA expression and suppressed the secretion of IL-1β by PBMCs. The findings indicate that G2013 may exert its regulatory effect under normal condition via Tollip in a dose dependence pathway. Our results demonstrated that G2013 had no profound impact on the protein expression of TLR2 and TLR4. Conclusion: In conclusion, our findings point to the immunomodulatory effect of G2013 on the TLR2 and TLR4 signaling cascade and cytokine production by PBMCs. These findings could lead to an establishment of new safe anti-inflammatory drugs in the future.
Keywords: Guluronic acid